(untitled) (Sains Humanika, 2016)
Urbanisation has given significant impact to various sectors, particularly in agriculture. Essentially, agricultural production activities depend heavily on land resources. At the same time, land is also needed as vital resources for the country development. Despite of the initiative of urbanism to better the country development process, it has raised concern among the land administrator regarding the status of the national’s food security. Food security has been threatened by the needs of the physical development due to urbanisation. Therefore, this article attempts to study the impact of urbanisation on the agriculture sector and examined the role of urbanism to safeguard the land resources for food security purposes. It is hope that, this article will form an inclusive understanding regarding the idea of urbanism in pursuing the betterment of an economic progress without compromising the needs for the national food security.